Mind the cat: Conservation management of a protected dominant scavenger indirectly affects an endangered apex predator. (May 2016) - Krofel, Miha; Jerina, Klemen
Abstract: Interspecific interactions are among the key factors influencing the structure of animal communities and have high relevance for conservation. However, managers, conservationists and decision-makers rarely consider the potential side-effects of single-species carnivore management for the conservation of other carnivores. We studied how management of protected brown bears ( Ursus arctos ) affected interspecific interactions with an endangered apex predator, the Eurasian lynx ( Lynx lynx ) in Slovenia. Due to large body size and superb olfactory abilities, bears are one of the most important dominant scavengers and regularly usurp kills from other large predators, a process known as kleptoparasitism. At the same time, bears throughout the world are usually actively managed through zone-specific culling regimes, supplemental feeding, and translocations. This can considerably alter bear densities and activity patterns and in turn influence interactions among carnivores. Overall, we observed that bear scavenging pressure resulted in substantial energetic losses for Eurasian lynx. The probability of lynx losing kills to bears ranged from 8 to 74% and strongly depended on local bear densities and monthly bear movement rates. Kleptoparasitic interaction intensity differed almost 3-fold between different bear management zones. Furthermore, the presence of a bear feeding site increased the odds of lynx losing kills by 5-fold compared to areas > 1000 m from these sites. We suggest that existing bear-feeding regimes should be reconsidered in order to reduce unwanted side-effects of this controversial practice on endangered apex predators. We also call attention to the importance of considering impacts of interspecific interactions in wildlife management and conservation. Highlights: We examined loss of roe deer carcasses killed by lynx to scavenging bears. Bear management measures indirectly increased loss of kills for the lynx. Kleptoparasitism increased cumulatively with bear densities and bear activity. Lynx lost more kills near bear feeding sites.